2017
DOI: 10.1074/jbc.m116.751685
|View full text |Cite
|
Sign up to set email alerts
|

Loss of N-Acetylgalactosaminyltransferase-4 Orchestrates Oncogenic MicroRNA-9 in Hepatocellular Carcinoma

Abstract: Edited by Gerald W. HartDeregulated expression of N-acetylgalactosaminyltransferases (GALNTs), which is responsible for the initial step of mucin-type O-glycosylation, could produce abnormal truncated O-glycans and thereby exert pivotal functions during malignant transformation. GALNT4 is one of the few isoforms preferring to catalyze partial GalNAc-glycosylated substrates and modify the sites not utilized by other known GALNTs. This study aims to evaluate the impact of GALNT4 expression on malignant transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…In hepatocellular carcinoma (HCC), GALNT1 levels are upregulated, and its depletion in a model of HCC causes a marked reduction in tumor formation (Huang et al, 2015). Yet others have shown that GALNT2 and -T4 are decreased in HCC (Liu et al, 2017;Wu et al, 2011), and it remains unclear whether these increases in expression are sufficient to exert a significant biological effect. Furthermore, these changes have not been correlated with Tn levels, and it is unlikely that increased GALNT expression alone could drive Tn levels (Ju et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC), GALNT1 levels are upregulated, and its depletion in a model of HCC causes a marked reduction in tumor formation (Huang et al, 2015). Yet others have shown that GALNT2 and -T4 are decreased in HCC (Liu et al, 2017;Wu et al, 2011), and it remains unclear whether these increases in expression are sufficient to exert a significant biological effect. Furthermore, these changes have not been correlated with Tn levels, and it is unlikely that increased GALNT expression alone could drive Tn levels (Ju et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…FUT8 transfers the fucose moiety from guanosine diphosphate-ÎČ-L-fucose to the innermost GlcNAc residue in N-glycans, denoted as core fucose [22]. Extensive literature indicates that alteration of glycosylation occurs during the progression of HCC [23,24]. Thus, FUT8 might have an important role in the development of HCC or in HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, miR-9-5p levels are elevated, and this miRNA enhances the stemness and anoikis resistance of cancer cells by targeting polypeptide N-acetylgalactosaminyltransferase 4 (GALNT4) ( Figure 1 and Table 1 ). Further investigations showed that GALNT4 attenuates the stemness and anchorage-independent survival of hepatocellular carcinoma cells in vitro and inhibits cancer cell growth in vivo partly via inactivating epidermal growth factor receptor (EGFR) [ 29 ].…”
Section: Mirnas Positively Regulating Anoikis Resistance and Anchomentioning
confidence: 99%